The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1063/1.1610248
|View full text |Cite
|
Sign up to set email alerts
|

Two stage oxidation in epitaxial Ni (111)/GaN (0001) thin films

Abstract: We present the oxidation process of epitaxial Ni (111)/GaN (0001) thin films studied by in situ synchrotron x-ray scattering, scanning electron microscopy, and transmission electron microscopy. By monitoring the evolution of the Ni (111) Bragg reflection, we reveal that two distinct oxidation processes occur. Initially, a continuous NiO layer of about 50 Å thickness is formed on the surface of Ni. The planar oxide layer saturates immediately and passivates the film from further surface oxidation. From this sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…For this 600 °C Ni nanoparticle oxidation, we think the "critical thickness" can be approximated by the above h(S1 end ) of the large Ni. This value is higher than the retraction of 3.5 nm reported for a Ni film oxidization at 300 °C, 50 consistent with the temperature effect on nucleation and oxide nuclei size. 49 Thus, since the radii of small Ni nanoparticles are smaller than the critical thickness under our oxidation condition, their oxidation did not proceed into the subsequent NiO thickening process (i.e., no Kirkendall voids were observed).…”
Section: Resultssupporting
confidence: 88%
“…For this 600 °C Ni nanoparticle oxidation, we think the "critical thickness" can be approximated by the above h(S1 end ) of the large Ni. This value is higher than the retraction of 3.5 nm reported for a Ni film oxidization at 300 °C, 50 consistent with the temperature effect on nucleation and oxide nuclei size. 49 Thus, since the radii of small Ni nanoparticles are smaller than the critical thickness under our oxidation condition, their oxidation did not proceed into the subsequent NiO thickening process (i.e., no Kirkendall voids were observed).…”
Section: Resultssupporting
confidence: 88%
“…8 Recently, NiO formed by thermal oxidation of Ni films has been proposed as the gate insulator in AlGaN/GaN HEMTs. 9 However, the thermal oxidation of Ni films can proceed through different stages 10,11 and can result into the formation of voids in the oxide layer. 10 This latter severely compromise the devices reliability and a uniform and epitaxial layer would certainly be preferred.…”
mentioning
confidence: 99%
“…Composite Interfaces 129 contact relaxes the Fermi-level pinning and suppresses the trap-assisted tunneling current. [11] Kang et al [12] reported that a NiO layer is easily formed when Ni is oxidized at temperature 300°C. NiO is also reported to behave as a p-type semiconductor with nickel vacancies and/or oxygen interstitials.…”
Section: Methodsmentioning
confidence: 98%